2014
DOI: 10.1212/wnl.0000000000000424
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal follow-up of SWEDD subjects in the PRECEPT Study

Abstract: Objective: To compare the clinical and imaging characteristics of those PRECEPT (Parkinson Research Examination of CEP-1347 Trial) subjects with a scan without evidence of dopaminergic deficit (SWEDD) to those with dopamine transporter (DAT) deficit scans at study baseline and during a 22-month follow-up.Methods: Baseline (n 5 799) and 22-month follow-up (n 5 701) [123 I] b-CIT SPECT scans were acquired. The percent change in [123 I] b-CIT striatal binding ratio, the percentage of subjects requiring dopaminerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
141
0
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 153 publications
(150 citation statements)
references
References 24 publications
4
141
0
5
Order By: Relevance
“…The eligibility assessment for DAT was based on visual assessment (the regulatory approved strategy for 123I Ioflupane) and comparison of the visual and quantitative outcomes shows outstanding agreement (Table S1). The imaging characteristics of the SWEDD subjects confirm prior reports that quantitative dopamine transporter assessments in this population are comparable to HC subjects 4. The wide range of DAT deficit among PD subjects (30–80% loss at baseline) suggest that additional characteristics may define subsets of PD that manifest PD symptoms after modest DAT loss compared to those requiring more severe DAT deficit 36, 37, 47.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The eligibility assessment for DAT was based on visual assessment (the regulatory approved strategy for 123I Ioflupane) and comparison of the visual and quantitative outcomes shows outstanding agreement (Table S1). The imaging characteristics of the SWEDD subjects confirm prior reports that quantitative dopamine transporter assessments in this population are comparable to HC subjects 4. The wide range of DAT deficit among PD subjects (30–80% loss at baseline) suggest that additional characteristics may define subsets of PD that manifest PD symptoms after modest DAT loss compared to those requiring more severe DAT deficit 36, 37, 47.…”
Section: Discussionsupporting
confidence: 79%
“…While recent data from clinical trials have demonstrated that subjects enrolled with SWEDD are unlikely to have PD,4 the clinical and biomarker characteristics of subjects with SWEDD have not been reported. The baseline PPMI data suggest that subjects with SWEDD have increased MDS‐UPDRS part 1 scores and greater degrees of depression, anxiety, and autonomic dysfunction compared to PD subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The four‐factor model could also differentiate SWEDD from PD, and likely predicted the conversion of SWEDD to PD. Of 31 SWEDD subjects, four converted to PD over the next 1–2 years, consistent with previous studies showing a conversion rate between 2 and 12% 14, 15, 16. All four were classified as “PD‐like” by the model, while none of those classified as “normal” converted to PD.…”
Section: Discussionsupporting
confidence: 86%
“…However, assessments taken in combination allow a greater sensitivity for determination of nigro-striatal impairment. In previous studies, an incorrect initial diagnosis of degenerative parkinsonism seems to account for a significant proportion of SWEDDs [12,13,23] and, in those studies where a second, follow-up scan has been performed, conversion from normal to abnormal was rather uncommon (8.3% in Ref. [13] and 12.5% in Ref.…”
Section: Discussionmentioning
confidence: 93%